The Relationship Between Service Quality and Public Satisfaction of Service Users at the Regional Education Office of North Sulawesi Province - Ering, Aurelia C.; Rares, Joyce J; Tasik, Femmy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
Good and quality public services are one indicator of the government's success in improving public welfare. The Regional Education Office of North Sulawesi Province, as one of the regional government administrators, plays a crucial role in providing quality public services to the community. However, there are still complaints from the public regarding the quality of services provided, such as unclear procedures, the behavior of individuals seeking profit, and poor service timeliness. This study aims to analyze the relationship between service quality and public satisfaction at the Regional Education Office of North Sulawesi Province. The research method used is quantitative with a cross-sectional study design, involving 363 respondents who are service users at the Regional Education Office of North Sulawesi Province. The results showed that the majority of respondents (50.1%) assessed the service quality as